A milestone in Islamic scholarship: Tawhidic epistemology congress at IIUM - Abdul Razak, Mohd Abbas (Human Assistance & Development International Inc. (HADI Inc.), 2025)
For the first time in the history of the International Islamic University Malaysia (IIUM), both academicians and students had the privilege to witness and take part in a marathon-like intellectual discourse that spanned several days. The five-day congress, held from 8th to 12th September, was organized by AHAS KIRKHS and marked a significant milestone for the university. The idea of bringing together all eleven departments of the Kulliyyah (Faculty) into one large congress was a major success, especially for the Dean, Prof. Dr. Hafiz Zakariya. The Chairperson, Dr. Rabiah Tul Adawiyah Mohamed Salleh, along with her dedicated team of academics, technicians, and students, did a fantastic job in ensuring the smooth running of the entire event. The congress was officially opened by Prof. Emeritus Datuk Dr. Osman Bakar, the Rector of IIUM, who was given the honour to grace the inaugural session and deliver a keynote address titled “Tawhidic Epistemology as the Catalyst for the Integration of Knowledge in the 21st Century.”